Subir e descer "batendo" : uma análise das práticas dos vendedores ambulantes nos espaços de mobilidade no BRT Move de Belo Horizonte - Bruna Barradas Cordeiro (2020)
This dissertation aims to understand the street commerce in the mobility spaces of BRT Move in Belo Horizonte and its Metropolitan Region, through the investigation of the daily practices of hawkers and their customers. For this, mobility is understood as movement socially produced and articulated, which involves meaningful practices and spaces for individuals who configure them on the move. Based on this understanding, one seeks to understand the daily practices of street vendors, who are those who maintain mobile services for mobile customers, creating an economy of mobility services. Through the triangulation of research techniques, which involved an analysis of secondary data from the National Household Sample Survey (PNAD), participant observation and in-depth interviews with hawkers from BRT MOVE in Belo Horizonte and its Metropolitan Region, one concludes that the hawking phenomenon, especially when it occurs in mobility spaces, cannot be understood without a relational approach, which takes into account the connections established with humans and nonhumans in the daily dynamics of work and movement. In addition, mobility shows itself as a key concept for understanding the relationship between street vendors and informality, crossing the narratives about learning the profession and transmitting daily organizational dynamics for negotiating sales spaces. Finally, BRT maintains some dynamics of distribution of sales circuits (pistas) that already existed on the streets, while transform others, in an intense negotiation process regarding the distribution of resources, which operates through social norms, in order to guarantee the maintenance of justice for these vendors.